Enhancing Innovation through Absorptive Capacity: The Moderating Role of Intellectual Capital - Maya Andriani; Bima Cinintya Pratama; Ani Kusbandiyah; Hardiyanto Wibowo (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study aims to investigate the impact of absorptive capacity on innovation within non-cyclical manufacturing companies in Indonesia and to examine the moderating role of intellectual capital.Method: The study employed a quantitative descriptive methodology, analyzing 176 data points derived from the annual financial statements of 38 non-cyclical manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sample was selected through purposive sampling based on specific criteria pertinent to the research objectives. Regression analysis was conducted using Stata, applying main and moderation models under fixed effects (as determined by the Hausman test), while passing diagnostic tests for heteroscedasticity and serial correlation to ensure validity and reliability.Result: The findings indicate that absorptive capacity significantly enhances innovation. Human capital and structural capital exert a positive and significant influence on innovation, whereas physical capital does not demonstrate a statistically significant direct effect. Nevertheless, the interaction of absorptive capacity with both structural capital and physical capital significantly bolsters innovation. Conversely, the interaction between absorptive capacity and human capital presents a negative moderating effect.Practical Implications for Economic Growth and Development: This study confirms that enhancing absorptive capacity, supported by intellectual capital, can improve innovation in non-cyclical manufacturing companies, ultimately strengthening industrial productivity and contributing to national economic growth.Originality/Value: This study provides an original contribution by empirically examining the moderating role of intellectual capital in the relationship between absorptive capacity and innovation, framed within the Resource-Based View theory.